Análise da propagação de trincas em estruturas metálicas predominantemente axissimétricas - Moita, Gray Farias (1990)
The purpose of this work is to realize an Evaluation of the Crack-Growth of Quasi-Axisymmetric Steel Structures by the FEM. Axisymmetric shell finite elements are used in the axisymmetric regions of the structure and 3-D shell elements in the regions where geometric deviations are found. The interface between these two regions is made through a "Transitional Element". The Crack-Growth Simulation is achieved by the Line-Spring Model and, with this procedure, the Stress Intensity Factor K, the J-Integral and other fracture parameters are obtained. Some applications are presented to access the performance of the implemented strategy. The advantages and the limitations of this strategy are also discussed.